Pemikiran Muhammad Quraish Shihab (Religius-Rasional) tentang Pendidikan Islam dan Relevansinya terhadap Dunia Modern - Daimah Daimah (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2018)
Religious-Rational educational thought is a philosophical school that combines religious perspectives with philosophical perspectives in describing education. One contemporary figure in this genre is Muhammad Quraish Shihab. According to him, the goal of Islamic education is to achieve the existence of Allah, that is to foster humanity to carry out its function as a servant of Allah and His Khalifah on this earth. With the library research method, the author analyzes the Islamic Education concept of Muhammad Quraish Shihab's perspective which is religious-rational and relevant to the modern world. As is known, today Islamic education has undergone a phase of significant change. These changes are nothing but the demands of a dynamic modern world with the times. Furthermore, Quraish Shihab emphasized that the development of Islamic education must be in line with developments in technology and information as demanded by the modern world.